DESIGN OF PILED RAFT FOUNDATION FOR ACADEMIC BUILDING OF BANDUNG INSTITUTE OF TECHNOLOGY USING FINITE ELEMENT METHOD - Kastara Pandega Pragata, Gibran
The construction of the Academic Building at Bandung Institute of Technology necessitates meticulous design of the piled raft foundation system. A rigorous analysis and design process is paramount to ensure the foundation's capacity to bear the anticipated structural loads. This design endeavor seeks to establish the ultimate bearing capacity of both the pile and raft components. This combined capacity will subsequently dictate the configuration and dimensional specifications of the piled raft foundation. Additionally, the design evaluates the total settlement experienced by the foundation and the apportionment of load distribution between the piles and the raft. The design methodology relies on software employing the finite element method. The analysis resulted in the optimal configuration of 110 piles spaced at 1.5 meters. The anticipated total settlement for this design is 2.63 centimeters. Furthermore, the load distribution analysis indicates that piles will carry 84% of the total load, with the remaining 16% borne by the raft.